Retinal Nerve Fiber Layer Thickness in Patients With Obstructive Sleep Apnea. Issue 5 (28th May 2023) - Devi, Thounaojam S.; Agrawal, Ajai; Gupta, Neeti; Gupta, Ravi; Samanta, Ramanuj; Nishant, Prateek
Abstract : Précis: Average and superior quadrant retinal nerve fiber layer thickness (RNFLT) was lower in the more severe obstructive sleep apnea (OSA) group and inversely associated with apnea-hypopnea index (AHI). OSA may have an impact on RNFLT. Purpose: The purpose of this study was to study the RNFLT using optical coherence tomography (OCT) in patients with different severities of OSA. Patients and Methods: In this hospital-based prospective cross-sectional study, 90 (90 eyes) newly diagnosed OSA patients aged 18 years or above were enrolled. Based on the AHI, there were 38.8%, 30%, and 31.1% cases of mild (AHI≥5 to <15), moderate (AHI≥15 to <30), and severe (AHI≥30) OSA, respectively. All the participants underwent a comprehensive ocular examination. OCT was done using CIRRUS HD-OCT 500 to measure the RNFLT. Results: The average RNFLT among the 3 OSA groups was significantly different ( P =0.002) and inversely associated with AHI ( P =0.02, r s =−0.16). Severe OSA had thinner average RNFLT than those with mild and moderate OSA ( P =0.01 and 0.003, respectively). Among the 4 quadrants observed, only the superior quadrant RNFLT among the 3 OSA groups was significantly different ( P <0.00001) and inversely associated with AHI ( P =0.01, r s =−0.17). Severe OSA had thinner superior quadrant RNFLT than those with moderate OSA ( P <0.01). The differences in the intraocular pressure among the 3 OSA groups were statistically significant ( P <0.0008). Patients with moderate and severe OSA had higher intraocular pressure than patients with mild OSA ( P =0.002 and 0.001, respectively). Conclusions: Attention should be paid to the patients with OSA as it may have an impact on RNFLT. OSA patients should be screened for glaucoma as early detection of glaucoma can reduce vision loss in these patients.